PENGARUH JUMLAH UANG BEREDAR TERHADAP INFLASI DI INDONESIA TAHUN 2006 – 2020 - Arisman Arisman; Fawza Rahmat; Maisarah Leli (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2023)
Inflation and interest rates are factors that can affect the exchange rate from the point of view of macroeconomic theory. Changes in the inflation rate can affect the demand and supply of a currency and therefore will affect the exchange rate of the Rupiah and changes in interest rates will have an effect on the flow of Indonesian state funds so that it affects the demand and supply of the Rupiah exchange rate. The problem in this research is how the influence of inflation and interest rates in Indonesia in the period 2006-2020. The discussion methodology uses quantitative methods with multiple analysis. The data used in this study is secondary data obtained from the website of the Indonesian Central Statistics Agency (BPS) in the form of TimeSeries for 15 years. Hypothesis testing was carried out using the T statistical test and the F statistical test using the EVIEWS 10 program. The results showed that in the partial test (t test) the value of the panel data regression analysis test showed that the t-count for the independent variable Inflation was -0.818360, while t table with a = 0.05 and df = (n-k), df = 12 where the t-table value is 2.17881 which means that the t-count value is smaller than the t-table value (0.818360 2.17881), then when viewed from the probability value, which is 0.4291 which is greater than 0.05 then Ho is accepted. This means that Inflation has no effect on the Exchange Rate. And the results of the panel data regression analysis test show that the t-count for the independent variable Interest Rate is -1.341310 while the t-table value with a = 0.05 is 2.16037 which means that the t-count is smaller than the t-table equal to (1,341310 2,17881) and when viewed from the probability value that is equal to 0.2047 which means greater than 0.05 then Ho is accepted. This means that it shows that the Interest Rate has no effect on the Exchange Rate. While the simultaneous test (f test) results in the output of Eviews, the calculated F value is 4.127236 while the F table with a level of a = 0.05 is 3.89, thus F count > F table (4.127236 > 3.89), then also seen from the probability value of 0.043248 which is smaller than the significance level of 0.05 so that Ho is rejected. This shows that the Inflation and Interest Rate variables together (simultaneously) have a significant effect on the Exchange Rate, so that the regression model can be used to predict the dependent variable.